Hope Lives in the Heart: Refugee & Immigrant Children’s Perceptions of Hope and Hope Engendering Sources during Early Years of Adjustment - Yohani, Sophie C.; Larsen, Denise J. (Canadian Journal of Counselling and Psychotherapy, 2009)
Children’s adjustment to resettlement countries is vitally important to future outcomes, yet little attention is given to the role of hope in this process. This research focused on expressions of hope in 10 refugee and immigrant children during early years of resettlement. Using case study methods that employed arts-based data collection, categories were constructed from participants’ visual images and associated narratives. Hope in newcomer children was conceptualized as a dynamic enduring trait that is intimately linked to each child’s life context. Further, three hope engendering sources were identified that facilitated an emotional connection to others, to self, and to the environment.